A Li–urine battery based on organic/aqueous hybrid electrolytes. Issue 7 (29th May 2019) - Lv, Yang; Shi, Shuai; Wang, Yahui; Yin, Huiming; Hu, Xun; Wu, Pingli; Gao, Guang-Gang; Liu, Hong; Liu, Xizheng
Abstract : Urea/urine as a renewable energy source is attracting extensive attention, which represents a promising prospect toward ensuring a clean environment and energy utilization. Abstract : Urea/urine as a renewable energy source is attracting extensive attention, which represents a promising prospect toward ensuring a clean environment and energy utilization. We herein report a new Li-urea battery architecture with organic and aqueous hybrid electrolytes. The concept of urea decomposition was first proposed in a Li-fuel battery. This low-cost portable device provides a new potential for power generation in the desert or remote regions.